The right to protection of personal data in the EU - Prlja Sanja (Strani pravni život, 2018)
The violation of the right to privacy and the need for protection has conditioned the development of regulations that govern these issues. The subject of work is the General Data Protection Regulation that the European Union passed in 2016 and will come into force on 28 May 2018. This new regulation regulates that question of protection of data in detail and creates new rights and obligations in this area. Besides other rights, individuals also acquire the right to transfer of data, and the right to be forgotten, while institutions that process data gain new obligations such as the impact assessment on privacy, integrated protection of privacy, appointment of an authorized person for protection of data, etc.